2015
DOI: 10.1016/j.otsr.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal survival rate after anterior cruciate ligament reconstruction

Abstract: IV, retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 16 publications
4
38
1
2
Order By: Relevance
“…Asahina et al [17] found that five patients requiring reoperation for failed meniscus repairs had no obvious cause. One possible cause of subsequent meniscal tears in the absence of trauma or sports injury is residual rotational instability despite ACLR [8]. Considering that 8/11 meniscal tears in our study were located at the MM PH, residual rotational instability may have played a role in the repeated shearing forces placed on the MM PH, which is similar to the situation in chronic ACL insufficiency [18][19][20][21].…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Asahina et al [17] found that five patients requiring reoperation for failed meniscus repairs had no obvious cause. One possible cause of subsequent meniscal tears in the absence of trauma or sports injury is residual rotational instability despite ACLR [8]. Considering that 8/11 meniscal tears in our study were located at the MM PH, residual rotational instability may have played a role in the repeated shearing forces placed on the MM PH, which is similar to the situation in chronic ACL insufficiency [18][19][20][21].…”
Section: Discussionmentioning
confidence: 63%
“…Values represent mean ± standard deviation BMI body mass index, STSD side-to-side differences, BPTB bone patellar tendon bone, A-B anterior horn to body, B-P body to posterior horn, A-P anterior horn to posterior horn a Hamstring autograft + tibialis allograft [1]. The MOON group's findings that discuss the inferior outcomes after MM injuries have been supported by the recent literature [7,8]. The Swedish National Knee Ligament Register study found that performance of a MM suture or resection at the time of ACLR was a predictor for non-satisfactory results [7].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Treatment of associated lesions: Three times the suture was associated with ligamentoplasty type DIDT ACL. This double repair is recommended by ROCHCONGAR [21] because he says, the effect is synergistic. So for him 80% of these double lesions should be repaired once at a time to optimize the final result.…”
Section: Diagnosismentioning
confidence: 99%